Force-dependent development of the myodural bridge in rats: The impact of Integrin α7 - Lu Zhang; Yun-Feng Liu; Mi Luo; Xue Song; Xin-yuan Zhang; Jing-Xian Sun; Jian-Fei Zhang; Xiao-Ying Yuan; Yan-Yan Chi; Ruo-Tong Zhang; Chan Li; Campbell Gilmore; et al. (PLoS ONE, 2025)
The myodural bridge (MDB) represents specialized fibrous structures establishing connectivity between suboccipital musculature and the spinal dura mater (SDM). The suboccipital muscles, ligaments, and myodural bridge fibers together form a functional unit known as the myodural bridge complex (MDBC). Mechanical stress from suboccipital muscles may contribute to MDB maturation. Integrin α7 (ITGA7) is critical for skeletal muscle attachment to connective tissues, and is involved in the transmission of lateral and longitudinal forces in skeletal muscle. Given the muscle force transmission characteristics of ITGA7 and the dependence of MDB development on force transmission, we hypothesized that ITGA7 serves as a crucial link between RCDmi and the MDB it emits, and may involve in the development of MDBC. To test this, neonatal Sprague-Dawley (SD) rats were randomly allocated to shRNA-ITGA7, shRNA-NC control, lentiviral vectors were injected into the dorsal atlanto-occipital interspace. ITGA7 suppression significantly impaired MDB development and maturation, manifesting as disrupted fiber assembly and RCDmi muscle dystrophy. Ultrastructural analysis revealed disorganized collagen fiber architecture and an abundance of fibroblasts, indicative of immature collagen fibers, further corroborated by Picrosirius red staining. Additionally, ITGA7 knockdown resulted in diminished RCDmi muscle force and altered ECM-related gene expression profiles. A key finding of our study is the importance of ITGA7 as a direct molecular link between suboccipital muscles and MDB, suggesting that mechanical forces from suboccipital musculature fundamentally influence MDB differentiation and maturation. These findings substantiate MDB’s role in force transmission to the SDM and by extension, advance our understanding of the molecular mechanisms underlying MDB development and its physiological significance.